(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to identify the role of employing artificial intelligence (AI) technologies in developing organizational agility in private universities located in Amman Governorate. The study population consisted of faculty and administrative staff at the following universities: Al-Zaytoonah University, University of Petra, and Middle East University, with a total number of (3040) members during the academic year (2024/2025). The study sample comprised (388) faculty and administrative members selected through a convenient sampling method. The descriptive correlational methodology was used to achieve the study objectives. The researchers developed the study instrument—a questionnaire—consisting of two axes: the first on artificial intelligence technologies, and the second on the development of organizational agility. The results indicated that the degree of employing artificial intelligence technologies in private universities in Amman Governorate from the employees’ perspective was high, with an overall mean score of (3.69). The results also showed that the level of organizational agility in these universities, from the employees’ point of view, was moderate, with a mean score of (3.34) Additionally, the results revealed no statistically significant differences at the significance level (α=0.05) in the mean scores of the study sample responses related to AI technologies in the domains of material requirements, technical requirements, and human requirements. However, statistically significant differences were found at (α=0.05) in the administrative requirements domain. Furthermore, the results showed no statistically significant differences at the significance level (α=0.05) attributable to the variables of gender, academic qualification, years of service, and job type in all domains. The findings also indicated a positive correlation between the employment of AI technologies and the development of organizational agility among employees in private universities in Amman Governorate, with a Pearson correlation coefficient of (0.862), which is statistically significant at (α=0.05) In light of these results, the researchers recommend that universities organize training courses and workshops aimed at enhancing the AI application skills of both academic and administrative staff.